Towards the Text: Between Theory and Practice - Yacoub, Zahra (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract: The term ' text ' has received special attention in contemporary linguistic studies, , especially with the emergence of what is known as Text science ' and ' text Linguistics ' and ' Grammar the text', despite the significant difference between Towards the text Textual Scientists, which has acquired different connotations as a result of the multiplicity of trends and theories, , But it can be considered as a unit or a systemic formation can be analyzed and detected coherence. It produced new concepts and trends that were a building block for the transition from the partial study to the comprehensive study and to move towards the sentence towards theGrammar text